Kajian Lafaz ditinjau dari Penunjukan Maknanya: Lafaz Amar (Makna, Penerapan dalam Nash dan Implikasi Hukum) - R, Rahmatullah; Masse, Rahman Ambo; M, Misbahuddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The pronunciation of amar (order) in the science of jurisprudence is one of the most central linguistic and legal instruments in the establishment of Islamic law. This study aims to analyze the meaning, form, and legal implications of the pronunciation amar in the nash-nash of the Qur’an and hadith, as well as to study how contextual and sectarian differences affect its understanding. The study used a qualitative approach with descriptive-analytic and library study-based methods. Data were analyzed through a thematic-comparative approach and studied within the framework of Shariah maqashid. The results of the study indicate that originally, utterance amar indicates obligation, yet it can change to recommendation, permissibility, or other meanings depending on the contextual qarinah. Differences between sects and social dynamics also influence the interpretation of this pronunciation. This study asserts that an understanding of amar Is not sufficient to rely on textual grammar alone, but must be integrated with maqashid, maslahat, and contemporary legal realities. This study contributes towards strengthening a responsive and relevant legal istinbat methodology in the Islamic legal system in Indonesia.